2020
DOI: 10.1038/s41598-020-68010-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation versus measurement of the glomerular filtration rate for kidney function assessment in patients with cancer undergoing cisplatin-based chemotherapy

Abstract: Glomerular filtration rate (GFR) assessment is indicated before every administration of cisplatin. The optimal modality for this purpose [GFR measurement by urinary Creatinine Clearance (uCrCl) versus GFR estimation (eGFR) by the CKD-EPI formula versus both] is unclear. We investigated whether eGFR only is safe in this setting. Paired uCrCl and eGFR determinations from 470 cisplatin cycles from 121 patients were analyzed [median age: 55 years; most frequent tumor site: genitourinary (45%); palliative treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Therefore, drug-induced toxicity is a vital problem in drug development and clinical drug application (Björnsson, 2016;Onakpoya et al, 2016). The use of many common drugs is limited by drug-induced organ injury, such as statins (Bouitbir et al, 2020), rifampicin (Chen et al, 2017), anthracyclines (Avila et al, 2018), and cisplatin (Klockl et al, 2020). Moreover, some drugs considered very safe can cause organ damage when they are taken in too high a dose or when idiosyncratic reaction occurs (Larson et al, 2005;Matsuo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, drug-induced toxicity is a vital problem in drug development and clinical drug application (Björnsson, 2016;Onakpoya et al, 2016). The use of many common drugs is limited by drug-induced organ injury, such as statins (Bouitbir et al, 2020), rifampicin (Chen et al, 2017), anthracyclines (Avila et al, 2018), and cisplatin (Klockl et al, 2020). Moreover, some drugs considered very safe can cause organ damage when they are taken in too high a dose or when idiosyncratic reaction occurs (Larson et al, 2005;Matsuo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Klockl et al concluded that it is useful to evaluate the renal function with only eGFR (namely omitting the burdensome timed urine collection for CrCl measurement) for patients with solid cancers who have received at least one cycle of cisplatin therapy ( Table 4 ) [ 121 ].…”
Section: Administration Of Chemotherapeutic Drugs In Ckd Patientsmentioning
confidence: 99%
“…45 Studies in cancer settings have shown eCrCl to be less reliable than the other equations when used by the bedside for dosage selection for kidney-excreted anticancer medications when compared with the use of mGFR. 26,47 In line with the newly developed International Consensus Guideline for Anticancer Drug Dosing in Kidney Dysfunction (ADDIKD) by eviQ and Cancer Institute NSW, it is recommended to use eGFR CKD-EPI as the standard and routine estimate of kidney function, and to use BSA-adjusted eGFR CKD-EPI for carboplatin dosing using the Calvert equation. 46 The ADDIKD was developed after an extensive and in-depth review of published literature.…”
Section: Dosing Of Anticancer Medicationsmentioning
confidence: 99%
“…The underestimate was demonstrated using inulin for gold standard GFR determination. 47 The ongoing changes in kidney function duration gestation and post-partum also make it difficult to predict steady state, limiting the usefulness of eGFR further. 64 Serial serum creatinine concentrations are recommended for monitoring kidney function in pregnancy, especially in acute illness.…”
Section: Medication Dosing In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation